Analisis Penatausahaan Aset Tetap dan Penerapannya Melalui Sistem Informasi Manajemen Aset Negara Barang Milik Negara (SIMAN BMN) Pada Rumah Sakit Umum Pusat H. Adam Malik Medan - Maria Rodetta Malau; Audrey M Siahaan; Danri Toni Siboro (Economic Reviews Journal, 2025)
This research discusses the administration of fixed assets managed by the H. Adam Malik Medan Central General Hospital using the State Asset Management Information System for State Property (SIMAN BMN) application, which aims to make the resulting goods report well presented. This research is a qualitative study with a descriptive design. The results showed that the H. Adam Malik Medan Central General Hospital as the Accounting Unit of the Goods User Authority has carried out the administration of fixed assets in accordance with applicable laws and regulations. However, after reclassifying into User Authoriation List-Heavily Damaged Goods/Lost Goods against BMN in a severely damaged/lost condition must propose the elimination of BMN to the Goods Manager, and archiving files related to bookkeeping, inventory, and reporting to be more concerned and more organized, and stored properly.